2020
DOI: 10.1101/2020.06.26.20139873
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Secondary pneumonia in critically ill ventilated patients with COVID-19

Abstract: Background Pandemic COVID-19 caused by the coronavirus SARS-CoV-2 has a high incidence of patients with severe acute respiratory syndrome (SARS). Many of these patients require admission to an intensive care unit (ICU) for invasive artificial ventilation and are at significant risk of developing a secondary, ventilator-associated pneumonia (VAP). Objectives To study the incidence of VAP, as well as differences in secondary infections, and bacterial lung microbiome composition of ventilated COVID-19 and non-CO… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 33 publications
4
21
1
Order By: Relevance
“…Therefore, since some patients may have experienced more than one VAP episode, we also cannot exclude an underestimation of the true incidence rate of VAP in critically ill COVID-19 patients. With regard to organisms isolated from deep respiratory specimens in patients with VAP in our series, the higher frequency of Gram-negative bacteria we registered is in line with recent data from other countries [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, since some patients may have experienced more than one VAP episode, we also cannot exclude an underestimation of the true incidence rate of VAP in critically ill COVID-19 patients. With regard to organisms isolated from deep respiratory specimens in patients with VAP in our series, the higher frequency of Gram-negative bacteria we registered is in line with recent data from other countries [ 22 , 26 , 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…There are different reasons that may explain this high incidence rate we registered. On the one hand, a truly increased risk of VAP in COVID-19 patients (which is in line with the high incidence rate of 28 episodes per 1000 ventilator-days registered in a recent UK study and with the high reported prevalence of 58% in a large cohort of 4244 critically ill patients with COVID-19 [ 22 , 23 ]), might be explained by different reasons: (i) a potential increased predisposition to bacterial superinfection, on the top of lung damage caused by COVID-19; (ii) the virus-related immunosuppressive effect with deep lymphopenia; (iii) the potential concomitant anti-inflammatory or immunosuppressive effect of steroids and biologic agents (e.g., anti-IL-6 receptor monoclonal antibodies) [ 24 , 25 ]. On the other hand, supporting instead a possible artefactual increase of the registered VAP incidence rate, we may have included some patients diagnosed with VAP who in reality did not have VAP, since we used a broad definition of VAP that is generally used for enrollment in clinical trials rather than for epidemiological purposes.…”
Section: Discussionsupporting
confidence: 60%
“…Third, significant deposition of microthrombi is common and may partly explain the proposed “L” (low lung weight, low elastance, and low inspiratory driving pressures) and “H” (high lung weight, high elastance, and high inspiratory driving pressures) ARDS phenotypes ( 81 ), although some experts have refuted the presence of the L phenotype. Fourth, COVID-19 patients are reported to have increased susceptibility to ventilator-associated pneumonia, for as yet undefined reasons compared with non–COVID-19 patients receiving invasive ventilation ( 82 ). Respiratory effects also occur along with MOF, profound alterations in coagulation, and hyperinflammatory cytokine profiles that are observed in other critical illnesses.…”
Section: Covid-19 Disease Mechanisms In Organ Failurementioning
confidence: 99%
“…The background of patients suffering from Coronavirus Disease 2019 (COVID-19) also appears to be highly compatible with the occurrence of IPA (9). ICU patients admitted for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and in uenza virus infections share speci c features, commonly described to increase the risk for ventilator associated pneumonia (10) and particularly fungal diseases including ARDS, possible corticosteroid administration, and systemic dysregulation of immune function (11). The incidence of COVID-19-associated pulmonary aspergillosis (CAPA) in ICU patients varies according to the major national cohorts from the United Kingdom (14.1%), Italy (27.7%), Germany (26.3%), the Netherlands (19.4%), and France (National MY-CO-VID clinical trial: 21.8%) (12)(13)(14)(15)(16) and are similar to the rate of IAPA observed in ICU cohorts (19%) from Belgium and the Netherlands (8).…”
Section: Introductionmentioning
confidence: 99%